Appropriate Antibiotic Use for Community-Acquired Pneumonia in Inpatient Settings and Its Impact on 30-days Readmission and Mortality Rate - Rafida Sofi Kamila1, Maftuchah Rochmanti2*, Arief Bakhtiar3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Community-Acquired Pneumonia (CAP) is a lower respiratory tract infection with bacteriaas the most frequent causative agent. Therapy for pneumonia includes appropriate antibiotic usage.Inappropriate antibiotic use supposedly increase 30-days readmission and mortality rate.Objective: To evaluate the antibiotic use and the impact of appropriate antibiotic use on the 30-daysreadmission and mortality of CAP patients in inpatient non-ICU settings.Method: A cross-sectional, analytic study was conducted. We collected data from Universitas Airlanggahospital’s medical record to obtain the details of antibiotic usage. Result were evaluated using the Gyssensalgorithm. A chi-square test was used to identify the impact of appropriate antibiotic use on the 30-daysreadmission and mortality.Result: A total of 90 patients with CAP fulfilled the inclusion criteria. One gram of ceftriaxone IV wasthe most prescribed antibiotic for therapy of CAP. The amount of appropriate antibiotic use is 85.6%. Fivepatients (5.6%) went through the 30-days readmission. There was no death reported. The statistical testbetween antibiotic use and 30-days readmission obtained p value=0.894 (p>0.05).Conclusion: There was no significant impact of appropriate antibiotic use on the 30-days readmission rateand the mortality rate could not be assessed.